Pemetaan Literasi Digital Masyarakat Dalam Menilai Kesiapan Akses Pelayanan Publik Digital di Kecamatan Sanga Desa - Indah, Sylvia Uly; Antoni, Darius; Saluza, Imelda (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2025)
Digital transformation in public service delivery requires community readiness in understanding and utilizing technology. At the village level, digital information systems such as Prodeskel, EPDeskel, Siskeudes, and SIPADES have been implemented by local governments to improve efficiency and transparency. However, low levels of digital literacy among citizens can hinder optimal use of these digital services. This study aims to map the digital literacy capabilities of the community in Sanga Desa Subdistrict as a basis for assessing their readiness to access technology-based public services. The research employed a quantitative approach using questionnaires based on the Digital Literacy Global Framework (UNESCO), which includes five dimensions: information and data literacy, communication and collaboration, digital content creation, safety, and problem-solving. A total of 500 respondents from 17 villages participated in the study. Data analysis using the digital literacy index and SPSS revealed that the majority of residents fall into the high and very high categories of digital literacy. However, some villages still demonstrate low readiness levels. This study recommends strengthening digital literacy training, developing digital infrastructure, and fostering collaboration between government and communities to support the success of digital transformation in rural public services